Performance of 3DOSEM and MAP algorithms for reconstructing low count SPECT acquisitions - Grootjans, Willem; Meeuwis, Antoi P.W.; Slump, Cornelis H.; de Geus-Oei, Lioe-Fee; Gotthardt, Martin; Visser, Eric P. (Zeitschrift für medizinische Physik, 2016)
Low count single photon emission computed tomography (SPECT) is becoming more important in view of whole body SPECT and reduction of radiation dose. In this study, we investigated the performance of several 3D ordered subset expectation maximization (3DOSEM) and maximum a posteriori (MAP) algorithms for reconstructing low count SPECT images. Phantom experiments were conducted using the National Electrical Manufacturers Association (NEMA) NU2 image quality (IQ) phantom. The background compartment of the phantom was filled with varying concentrations of pertechnetate and indiumchloride, simulating various clinical imaging conditions. Images were acquired using a hybrid SPECT/CT scanner and reconstructed with 3DOSEM and MAP reconstruction algorithms implemented in Siemens Syngo MI.SPECT (Flash3D) and Hermes Hybrid Recon Oncology (Hyrid Recon 3DOSEM and MAP). Image analysis was performed by calculating the contrast recovery coefficient (CRC),percentage background variability (N%), and contrast-to-noise ratio (CNR), defined as the ratio between CRC and N%. Furthermore, image distortion is characterized by calculating the aspect ratio (AR) of ellipses fitted to the hot spheres. Additionally, the performance of these algorithms to reconstruct clinical images was investigated. Images reconstructed with 3DOSEM algorithms demonstrated superior image quality in terms of contrast and resolution recovery when compared to images reconstructed with filtered-back-projection (FBP), OSEM and 2DOSEM. However, occurrence of correlated noise patterns and image distortions significantly deteriorated the quality of 3DOSEM reconstructed images. The mean AR for the 37, 28, 22, and 17mm spheres was 1.3, 1.3, 1.6, and 1.7 respectively. The mean N% increase in high and low count Flash3D and Hybrid Recon 3DOSEM from 5.9% and 4.0% to 11.1% and 9.0%, respectively. Similarly, the mean CNR decreased in high and low count Flash3D and Hybrid Recon 3DOSEM from 8.7 and 8.8 to 3.6 and 4.2, respectively. Regularization with smoothing priors could suppress these noise patterns at the cost of reduced image contrast. The mean N% was 6.4% and 6.8% for low count QSP and MRP MAP reconstructed images. Alternatively, regularization with an anatomical Bowhser prior resulted in sharp images with high contrast, limited image distortion, and low N% of 8.3% in low count images, although some image artifacts did occur. Analysis of clinical images suggested that the same effects occur in clinical imaging. Image quality of low count SPECT acquisitions reconstructed with modern 3DOSEM algorithms is deteriorated by the occurrence of correlated noise patterns and image distortions. The artifacts observed in the phantom experiments can also occur in clinical imaging. Eine adäquate Rekonstruktion von Single-Photon-Emission-Computed-Tomography(SPECT)-Bildern mit geringer Zählstatistik wird zunehmend wichtiger, insbesondere in Hinsicht auf die Ganzkörper-SPECT und eine Reduktion der Strahlendosis. In dieser Studie wurde die Leistung von verschiedenen Algorithmen bei der Rekonstruktion von Tomographien mit geringer Zählstatistik verglichen. Phantom-Experimente wurden mit dem National-Electrical-Manufacturers-Association(NEMA)-NU2-Bildqualitäts(IQ)-Phantom ausgeführt. Verschiedene klinische Situationen wurden durch Füllen des Hintergrunds des Phantoms mit variierenden Konzentrationen von Technetium-Pertechnetat und Indiumchlorid simuliert. Tomographien wurden mit einem SPECT/CT-Scanner acquiriert und mit verschiedenen Algorithmen (ordered subset expectation maximization (OSEM), maximum a posteriori (MAP) und gefilterte Rückprojektion) rekonstruiert. Die für die 3DOSEM-Rekonstruktion verwendeten Algorithmen waren Flash3D (implementiert in Siemens Syngo MI.SPECT) und Hybrid Recon 3DOSEM (implementiert in Hermes Hybrid Recon Oncology). Die Bildqualität wurde durch Berechnung der Kontrastwiederherstellungskoeffizienten (CRC), der Prozent-Hintergundvariabilität (N%) und der Kontrast-Rausch-Verhältnisse (CNR), definiert als das Verhältnis der CRC und N%, quantifiziert. Elliptische Verzerrungen wurden durch die Berechnung der Achsenverhältnisse (AR) ermittelt. Darüber hinaus wurden die verschiedenen Algorithmen anhand der resultierenden Bildqualität von klinischen SPECT-Studien miteinander verglichen. Bilder, die mit 3DOSEM-Algorithmen rekonstruiert wurden, zeigten eine überlegene Bildqualität in Bezug auf Kontrast und Auflösung im Vergleich zu Bildern, die mit gefilterter Rückprojektion, OSEM und 2DOSEM rekonstruiert wurden. Allerdings treten korrelierte Rauschmuster und Bildverzerrungen auf, welche die Qualität der mit 3DOSEM rekonstruierten Bilder verschlechtert. Die Mittelwerte der AR für die 37-28-22- und 17-mm Kugeln waren 1.3, 1.3, 1.6, und 1.7. Die Hintergrundvariabilität in Flash3D und Hybrid-Recon-3DOSEM-Bildern mit hoher und geringer Zählstatistik stieg von 5.9% und 4.0% auf 11.1% und 9.0%. Der Mittelwert der CNR in Flash3D- und Hybrid-Recon-3DOSEM-Bildern mit hoher und niedriger Zählstatistik verminderte sich von 8.7 und 8.8 auf 3.6 und 4.2. Regularisierung mit smoothing priors können diese Rauschmuster auf Kosten eines reduzierten Bildkontrasts unterdrücken. Wenn die Regularisierung mit einer anatomischen Bowsher prior ausgeführt wurde, ergaben sich scharfe Bilder mit hohem Kontrast, begrenzten Bildverzerrungen und geringer Hintergrund-Variabilität von 8.3%, jedoch können in diesen Bildern Artefakte auftreten. Eine Analyse von klinischen SPECT-Aufnahmen zeigten die gleichen Bildartefakte. Die Bildqualität der SPECT-Bilder mit niedriger Zählstatistik, welche mit modernen 3DOSEM-Algorithmen rekonstruiert werden, wird durch das Auftreten von korrelierten Rauschmustern und Bildverzerrungen verschlechtert. Die bei den Phantomaufnahmen beobachteten Bildartefakte treten auch bei klinischen SPECT-Bildern auf.